Pengaruh Inovasi Produk dan Kemasan Produk Terhadap Kepuasan Konsumen di Lestari Kopi Sampit - Staciana, Athalia (Universitas Darwan Ali, 2023)
The current competition in coffee shops makes business people create strategies to become the best of the best. One of the strategies implemented by Kopi Lestari is to innovate new products in the form of Pistachio Matcha, Cream Cheese Matcha, and the most unique is KombuchaThis research aims to analyze the effect of product innovation and product packaging on consumer satisfaction at Lestari Kopi Sampit. This research was conducted using a quantitive method. The sample used for this research consisted of 85 respondents who were selected through accidental sampling technique from Lestari Kopi customer who had visited more than once. The research instrument used for this study was a questionnaire, which consisted of structured questions relating to the influence of product innovation and product packaging in influencing consumer satisfaction at Lestari Kopi Sampit. The result indicate that product innovation and product packaging have a significant positive effect on consumer satisfaction at Lestari Kopi Sampit.